Effect of Acupuncture Needling on Anmian Point with Deep Relaxation Technique for Insomnia: A Randomized Controlled Trial - K, Dhanalakshmi; P S, Swathi; Das, Pranab (Indian Journal of Integrative Medicine, 2025)
Background: Insomnia, known as sleeplessness, is a sleep disorder where people have trouble sleeping. Long latency, Frequent nocturnal awakenings, Prolonged periods of wakefulness during the sleep phase, or even frequent transient arousals are all signs of insomnia. The deep relaxation technique (DRT), one such mind-body relaxation technique, improves sleep quality. Similarly, Acupuncture is found to treat patients suffering from insomnia to improve the quality of sleep. Objective: The current study evaluated the efficacy of Acupuncture and Deep relaxation technique (DRT) in improving sleep quality. Materials and methods: 50 subjects, both male and female, were randomly allocated to the experiment group or control group. The experiment group received single-point acupuncture with DRT for 20 minutes/day for two weeks. The control group received sham acupuncture and supine rest for 20 minutes/day for two weeks. Baseline and post-assessments of both groups were taken on day 1 and day 14, respectively. Statistical analysis was performed using repeated measures of analysis of variance (ANOVA) followed by post hoc analysis with Bonferroni adjustments for multiple comparisons. Results: There was a statistically significant difference noted in the pre and post-tests of both the groups, such as subjective sleep quality, sleep efficiency, sleep latency, daytime dysfunction, global Pittsburgh Sleep Quality Index (PSQI) score, and perceived stress by (PSS). Conclusion: Acupuncture and DRT can effectively improve sleep quality.